Neuroimaging Pathognomonic Manifestations Of Cerebral Amyloid Angiopathy - Severyn, Yu. (Psychiatry, Neurology and Medical Psychology, 2016)
The article concerns the problem of cerebral amyloid angiopathy (CAA), a chronic progressive disease of the brain vessels, characterized by the deposition of β-amyloid peptide in the walls of arteries, arterioles, capillaries and venules. The data on etiology, pathogenesis, clinical manifestations, diagnosis and treatment of the disease are given. Particular attention to the neuroimaging diagnostics, that allow to identify the disease at an early stage with a non-invasive method is paid. Radial diagnostic criteria of CAA, which are prognostically important for diagnosis, evaluation of the course and prognosis of the disease are obtained.